The epigenetic regulation of crosstalk between cardiac fibroblasts and other cardiac cell types during stress - Kraus, Lindsay; Fredericks, Synclare; Scheeler, Katelyn (Frontiers in Cardiovascular Medicine, 2025)
With the global impact of cardiovascular disease, there is a dire need to understand the mechanisms in the heart during injury and stress. It has been shown that the regulation of the extracellular matrix via cardiac fibroblasts plays a major role in the progression of heart failure and worsening function of the heart. Importantly, it has been suggested that crosstalk between other cardiac cells like cardiomyocytes, immune cells, and endothelial cells are influenced by the pathological function of the fibroblasts. This decline in function across all cardiac cells is seemingly irreversible. However, epigenetic mechanisms have been shown to regulate functionality across cardiac cells and improve outcomes during stress or injury. This epigenetic regulation has also been shown to control communication between different cell types and influence the role of multiple cardiac cell types during injury. The goal of this review is to summarize and discuss the current research of epigenetic regulation of cardiac fibroblasts and the subsequent crosstalk with other cardiac cell types in cardiovascular disease states.